WASH Poor in a Water-Rich Country : A Diagnostic of Water, Sanitation, Hygiene, and Poverty in the Democratic Republic of Congo - World Bank (World Bank, Washington, DC, 2017)
The Democratic Republic of Congo (DRC) is among the five poorest countries in the world, whether measured by poverty rate or number of poor. Political instability and rapid demographic growth—the second highest in Africa—have driven an increase in the total number of poor that puts extreme pressure on the country’s derelict infrastructure. Access to improved water, sanitation, and hygiene (WASH) services is low, with particularly dramatic shortfalls among the poorest and rural dwellers, but a pervasive lack of truly safe services even among wealthier and urban households. Water contamination is common even among households with access to piped water in major urban areas, and nearly universal in the rural areas surveyed by this diagnostic. This contamination is making WASH a key contributing factor to a silent emergency that is placing DRC’s poor and rapidly growing population at risk of permanent disconnect: widespread malnutrition. Malnutrition is especially common among DRC’s children (43 percent in 2014) and has been shown to have irreversible negative effects on physical and cognitive development. This diagnostic analyses these trends and links them to institutional weaknesses in the WASH sector, in particular institutional fragmentation, weak capacity, and a bias toward specific institutions and services. Opportunities for improvement are analyzed and condensed into six clear messages that provide guidance on the way forward for the WASH sector in the DRC.